A BOOST–CHEMKIN Framework for HCCI Combustion and Emission Analysis of Methyl Decanoate/Di-n-Butyl Ether Blends in a Marine Diesel Engine - Peiyuan Wang; Jianghua Sui; Shiye Wang (Journal of Marine Science and Engineering, 2026)
Diesel engine emissions remain a concern because of their environmental and health impacts. Homogeneous charge compression ignition experiments on low-speed two-stroke marine diesel engines are costly, risky, and limited by scarce transient data. To address this issue, a one-dimensional/zero-dimensional AVL BOOST-ANSYS CHEMKIN coupled framework was established for an MAN B&W 6S50MC low-speed two-stroke marine diesel engine, providing a reasonable approach under data-limited conditions. The framework provided key initial conditions for detailed chemical-kinetic analysis and was used to examine methyl decanoate (MD)/di-n-butyl ether (DBE) blends with 0–20% DBE. The results indicate that DBE addition alters the balance between aromatic growth and oxidative removal and enhances low-temperature chain branching, while the increased peak temperature raises nitrogen oxides (NOX) emissions. To relate these mechanistic results to engineering evaluation, the weighting scheme of the IMO NOX Technical Code 2008 test cycle was introduced. Pyrene and its isomers and NOX were treated by weighted normalization, followed by Pareto analysis and TOPSIS methods. MD90 (90 vol% MD and 10 vol% DBE) showed the best emissions trade-off over a wide range of weighting settings, which may provide useful guidance for optimizing oxygenated fuel blending ratios.